ENHANCING ENGLISH ESSAY WRITING THROUGH AI-BASED DIGITAL TOOLS: INSIGHTS FROM INDONESIAN EFL STUDENTS - Muh. Al Fachrizah Fitra; Sultan Baa; Samtidar Samtidar; Yunitari Mustikawati; Ulvah Sari (Universitas Bina Bangsa Getsempena, 2026)
The increasing integration of artificial intelligence (AI)-based digital tools has reshaped English writing instruction, particularly in EFL contexts where students often struggle with idea development, linguistic accuracy, vocabulary use, and textual coherence. This study investigates how Indonesian senior high school students utilize AI-based digital tools in writing English essays, with particular attention to ChatGPT, Grammarly, and DeepL. Employing a qualitative descriptive design, the study analyzed 28 final essays written by twelfth-grade students in the Language Studies major at a public senior high school in Makassar, Indonesia. The essays were examined through thematic analysis using four analytical dimensions: structure and organization, grammar and syntax, vocabulary use, and coherence and cohesion. The findings reveal that AI-based tools contributed most visibly to improved essay organization, lexical expansion, and local textual flow. Students’ essays showed clearer paragraph sequencing, more academic and topic-specific vocabulary, and stronger use of cohesive devices. However, grammatical accuracy and idiomatic control remained uneven, with persistent issues such as tense inconsistency, article errors, translation-like syntax, and mechanical transitions. This study contributes to AI-assisted EFL writing research by offering text-based evidence from an underexplored secondary-school context and by conceptualizing AI support as a multi-tool writing ecology rather than a single technological intervention.